College Student Learning Preparedness: Do Time Management Skills and Sleep Quality Matter? - Nora Novita; Masnur Alam; Eko Sujadi (PT ARRUS Intelektual Indonesia, 2024)
The success of the learning process is more probable when students demonstrate high levels of readiness to learn. However, evidence from previous studies suggests that not all students possess this readiness. This study aims to investigate the individual and combined effects of time management and sleep quality on students' preparedness for learning. Utilizing a quantitative survey design, the research engaged 178 students from the Kerinci State Islamic Institute. Sample size determination followed the Krejcie & Morgan formula, with sample selection executed through Simple Random Sampling. Data collection incorporated the Self-Directed Learning Readiness Scale, Time Management Scale, and Sleep Quality Scale. Analysis of the research data involved simple and multiple linear regression. Results indicate that both time management and learning readiness significantly influence students' preparedness for learning, with time management exerting a stronger impact. This research carries substantial implications for addressing students' learning readiness challenges through the promotion of effective time management strategies and the assurance of adequate sleep quality. Such interventions can be efficiently implemented through higher education's guidance and counseling services, involving counselors and additional support structures.